Pendidikan Dasar Musik: Pendampingan dan Pelatihan Notasi Dasar kepada Remaja di GPT “MARANATHA” Desa Penda Pilang – Tumbang Manyangan - Sion Saputra; Talizaro Tafonao (Jurnal Nusantara Mengabdi, 2022)
Purpose: The purpose of this dedication is to train and prepare teenagers to have notation reading skills and understand basic notation. Research Methodology: This dedication was carried out by 1 trainer and followed by 10 teenaders who became participant/partner. On the process, this mentoring and training method is carried out by means of lectures, simulations, questions and answers, and exercises. Result: The results of this service activity have resulted in backing vocal services that have qualified abilities ranging from 80%. This can be seen when the participants/partners can read and understand the song notation well. Limitations: The limitation in this dedications is the lack of human resources from trainers. Ideally, mentoring and trainong of basic notation requires two trainers, because if one trainer is absent, the other trainer can still provide mentoring and training. Contribution: This activity make a good contribution to the church GPT “MARANATHA” Penda Pilang – Tumbang Manyangan villages, and was very effective among teenagers to foster the interests and talents of each participant/partner.